Management to Create Child-Friendly Schools in Early Childhood Islamic Education Institutions - Alfina, Alisa; Afifah, Sofia Nur; Anwar, Rosyida Nurul; Ramadhani, Nur Vita Sari Eka; Putri, Renita Luthfiani (PG-PAUD Trunojoyo, 2024)
Child-friendly schools are very important because they provide a safe and supportive environment for children's development. Currently, child-friendly schools are being promoted in all educational institutions in Madiun Regency. The government has issued a decree. regarding child-friendly schools in Early Childhood Education institutions that meet the requirements and are able to realize Child-Friendly Schools. TK IT Nur Al Izhar is one of the Islamic-based PAUD institutions that has been appointed as a Child-Friendly School by the local government. This study aims to determine the management in realizing child-friendly schools in Islamic-Based PAUD. The research method is a qualitative approach. Data collection through observation, interviews and documentation. Data analysis techniques in the form of data reduction, data presentation, and withdrawal. The results of the study found that PAUD institutions have not fully implemented child-friendly schools, especially the lack of teacher training related to children's rights and the lack of socialization of child-friendly schools to parents. Some obstacles in realizing Child-Friendly Schools, namely the mindset of Child-Friendly Schools that have not been fully understood by all teachers and non-teaching staff, parents of students who do not understand Child-Friendly Schools. Child-friendly school management as part of an effort to consistently provide comfortable, safe education for children.